COMPETENCY APPROACH IN THE PROFESSIONAL ACTIVITY OF A TRANSLATOR (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
One of the relevant areas of the educational paradigm today is entering a competency-based approach, the formation of the ability of the translator’s personal qualities, the formation of the person’s ability to use existing knowledge, skills and abilities.